ENHANCING HUMAN SKILLS THROUGH INNOVATIVE PEDAGOGIES: INTEGRATING TBPL AND DESIGN THINKING IN INDONESIAN HIGHER EDUCATION - Alam, Helmy Syakh; Yupita, Linda; Waheed, Syed Abdul; Gilani, Nadia (Universitas Muhammadiyah Surakarta, 2025)
The rapid progression in digital technologies and endless industrial disruption necessitate that higher education institutions change from the classical paradigm of knowledge transfer toward one that enhances adaptive human skills. This article discusses the integration of Team-Based Project Learning (TBPL) and Design Thinking as an innovative teaching method for enhancing human skills, e.g., collaboration, communication, critical thinking, empathy, and problem-solving. Two hundred twenty-nine students at Primakara University were involved in the learning model, and data were collected through a structured questionnaire; they were analyzed using descriptive statistics with the aid of SPSS version 26 based on mean scores and rank indicators of the skill structure. All skill dimensions measured in this study were rated above 3.00 on a 1–4 Likert scale, which indicates an encouraging perception from the students. Highest-scored dimensions included: Lecturer Support (3.48) and Ability to Face Challenges (3.38), whereas Learning Facility Support (3.20) and Project Theme Relevance (3.12) scores recorded were relatively lower. It appears that the TBPL and Design Thinking integration have constructive contributions toward the development of non-cognitive competencies concerning the 21st century. The findings give empirical implications for the universities to design learning environments with an explicit intent to embed collaboration, empathy, and problem-solving as key educational outcomes.